Adsorption of Copper Ions from Aqueous Solution Using Raw and Modified Can Papyrus: Experimental and Kinetic Study - Saed, Usama Akram; Jaleel, Noor Sabah A. (Al-Nahrain Journal for Engineering Sciences, 2017)
The adsorptions of copper ions from aqueous solution by can papyrus were studied using batch and continuous adsorption. It has been improved surface area and efficiency of the cane papyrus using urea and thiurea at different concentrations through stirring in period of time with mixer. Results proved that cane papyrus very well in the adsorption of metal through the study of important variables and influences such as the contact time, pH in addition to the initial concentration. It was found that the effect of pH at 6 to 7 better than acid or base solution also found that the best time for adsorption to reach equilibrium is 90min and there is no effect of temperature significantly on the results observed, studied the effect of weight of the cane where found that 0.4g best weight. After treatment with urea and thiurea the results improved from the 56% removal by natural cane, 61% for urea modified and 68% for thiurea modified. For continuous adsorption the results shows that when the flow rate increase in constant bed of adsorbent the breakthrough decrease. As well as the best curve was obtained using a cane modified with thiurea weighing 2.5g in a continuous flow rate where the breakthrough curve is start from 25min to 175min. The results was applied to Langmuir and Freundlich adsorption isotherms, the results fitted will to both at correlation coefficients 0.971 and 0.9066 for Langmiur and Freundlich respectively. Pseudo second order was applied and gives better results for adsorption where R2 is 0.9941 while for pseudo first order R2 is 0.136.